Britain, Brexit and Euroscepticism: Anthropological Perspectives on Angry Politics, Technopopulism and the UK Referendum. Issue 2 (1st September 2021) - Shore, Cris
Abstract: When history books about Brexit are written a key question asked will be ' how did it happen?' How did a country renowned for stable governments, pragmatism and diplomacy produce a chaotic outcome so harmful to its economic interests and international standing? This article examines the factors that produced Brexit by analysing its political and historical context, the main campaign groups and their communication strategies. Drawing on the work of Verdery (1999), Maskovsky and Bjork-James (2020) and other anthropologists, I suggest we need to look beyond conventional political science concepts and consider Brexit in terms of 'enchantment', 'angry politics' and 'technopopulism'. I conclude that while Brexit provides a window for analysing fault lines in contemporary Britain, it also highlights problems in the EU, its austerity politics and democratic deficit.